Forming limit analysis of Mg-2Zn-1.2Al-0.2Ca-0.2RE alloy sheet using ductile fracture models. (August 2020) - Li, Fei-Fan; Fang, Gang; Qian, Ling-Yun
This work was aimed to experimentally and theoretically investigate the formability of a new magnesium alloy sheet at room temperature. The fracture forming limit diagram was predicted by MMC3 and DF2014 models, where the non-linear strain path effect was taken into account by means of damage accumulation law. In order to obtain the instantaneous values of the stress triaxiality and the Lode parameter during the deformation process, strains tracked by digital image correlation technique were transformed into stresses based on the constitutive equations. The fracture forming limit diagram predicted by the fracture models was compared with the forming limits obtained by ball punch deformation tests. The prediction errors were evaluated by the accumulative damage values, which verified the advantages of ductile fracture models in predicting the forming limits of the magnesium alloy sheets.